Virtual Reality Foot Reflexology (VRST): A New Alternative in Foot Reflexology - Chimeremeze Okere, Hector; A. Abu Bakar, Juliana; Che Mat, Ruzinoor (International Journal of Engineering and Technology, 2018)
Virtual reality stress therapy (VRST) is an innovative and emerging concept that provides effective modality for relaxation and stress therapy by allowing users to be exposed to similar stimuli as their real-world counterparts using a computer-generated virtual environment. Foot reflexology has been widely used to improve quality of life and well-being, reflected in numerous benefits such as stress relief, distress, insomnia relief, potential diagnostic tool, sleeping disorder, and as a complementary treatment tool. This paper presents the varying alternatives in foot reflexology stress therapy applications and the opportunities VR offers the therapy. Virtual reality foot reflexology stress therapy application utilized VR technologies of visual and aural interactivity, coupled in a Head-Mounted-Display (HMD), alongside a reflexology artifact/device for haptic interaction for relaxation and stress relief. Implications and Future works were also discussed.Â